INTERTEXTUALITY IN RUSSIAN POETRY BASED ON THE WORKS OF F.I. TYUTCHEV AND A. S. PUSHKIN - Dinara Rifkatovna Aflyatunova; Nigina Bakhtiyarovna Rustamova (Galaxy International Interdisciplinary Research Journal, 2022)
This article examines intertextuality as a linguistic phenomenon in Russian poetry based on the works of F.I. Tyutchev and A.S. Pushkin. The definition is given: the structural organization of the artistic poetic text, the term intertextuality as a category of artistic text and the poetic word in the intertext under the influence of precedent texts, which not only enriches its semantic structure by "incrementing" new meanings, but also changes the semantics of the poetic work as a whole.